Validation of sensor-based game analysis tools in tennis - Edelmann-Nusser, A.; Raschke, A.; Bentz, A.; Montenbruck, S.; Edelmann-Nusser, J.; Lames, M. (International Journal of Computer Science in Sport, 2019)
Three inertial measurement unit (IMU) based tennis sensor systems from BABOLAT (PURE DRIVE PLAY, POP) and HEAD (Tennis Sensor) and a camera-based system (PlaySight) were tested with respect to the question whether the information about the number of strokes by swing type and spin type in training exercises and/or matches and the average as well as the maximum speed of the service per session are reliable. Subsequently, the question whether the mechanical properties of the BABOLAT PURE DRIVE PLAY racket are the same as the mechanical properties of the BABOLAT PURE DRIVE racket without IMU was addressed.